We're not sure what the question means by "root". It may be what's usually
referred to as the "solution" of the equation ... the number that 'a' must be in
order to make the equation a true statement. Here's how to find the 'solution':
- 5a - 3 = 3a
Add 5a to each side:
- 3 = 8a
Divide each side by 8:
- 3/8 = a
13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2
9a2=24a-16 9a2-24a+16=0 (3a-4)(3a-4)=0 3a-4=0 a=4/3 double root
(3 x 3) - 6 = 3 3a-6=3 3a=3+6 3a=9 a=9/3 a=3
3a = 1a = 1/3 (a third)
In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)
If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1
Answer to: 5a + 1 = a - 3a = -1
13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2
a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100
-8a + 3a = (-8 + 3)a = (5)a = 5a
5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4
what is 5a x 3 x 2b
3a2 - 16a + 5 = 3a2 - 15a - a + 5 = 3a(a -5) - 1(a -5) = (3a - 1)(a - 5)
9a2=24a-16 9a2-24a+16=0 (3a-4)(3a-4)=0 3a-4=0 a=4/3 double root
Three consecutive even integers can be represented by a-2, a & a+2.Five times the first is 5a-10. Three times the second is 3a.5a-10 is 14 more than 3a, so 5a-10 = 3a+14Adding 10 to both sides: 5a = 3a+24Taking 3a from both sides: 2a = 24Therefore a=12The three consecutive even integers are 22, 24 and 26.
(3 x 3) - 6 = 3 3a-6=3 3a=3+6 3a=9 a=9/3 a=3
It is not clear whether the question is 3a + 4a + 5a + 6a^3 which would be 12a + 6a^3 or 3a + 4a + 5a + (6a)^3 = 12a + 216a^3 or (3a + 4a + 5a + 6a)^3 = 5832*a^3 But none of these really require summation notation!